Risk Assessment of Occupational Health and Safety in Lifting Operations Using the HIRADC Method: A Case Study in Oil and Gas Construction - Gultom, Dessy Chaterina Ullyma; Adam, Ichsan; Sukwika, Tatan (Journal of Applied Management Research, 2025)
The complexity of lifting operations in oil and gas refinery construction presents significant occupational safety and health risks. This study aims to enhance the effectiveness of Hazard Identification, Risk Assessment, and Determining Control (HIRADC) by identifying existing hazards, assessing inherent and residual risks, and proposing improved mitigation measures. Based on the HIRADC analysis conducted at oil and gas refinery construction, initial findings showed five high-risk activities. After implementing additional control measures, including installing hard barricades, proper signaling during lifting, and equipment checks, the residual risk levels were reduced to moderate-to-high categories. Moreover, the study identified an additional unrecorded activity in the original HIRADC: job preparation and work method validation, which was subsequently integrated into the revised framework. The study concludes that improving the HIRADC process, supported by routine inspections, proper use of personal protective equipment (PPE), and the placement of HSSE signs, plays a crucial role in preventing workplace accidents caused by unsafe actions, mechanical hazards and ergonomic issues during lifting operations.